PHYTOCHEMISTRY, PHARMACOLOGY AND ETHNOMEDICINAL USES OF FICUS THONNINGII (BLUME MORACEAE): A REVIEW - Dangarembizi, Rachael; Erlwanger, Kennedy H; Moyo, Davison; Chivandi, Eliton (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
The common wild fig, Ficus thonningii, is extensively used in African ethnomedicine for treating a number of disease conditions which include diarrhoea, urinary tract infections, diabetes mellitus, gonorrhoea, respiratory infections, and mental illnesses. This review aims to present a logical analysis of the nutritional, phytochemical and pharmacological properties of F. thonningii in relation to its therapeutic applications. A bibliographic analysis of the uses, phytochemical constituents and phytophamacological properties of Ficus thonningii was carried out using published papers, medicinal plant databases and various ethnobotanical and ethnopharmacological books. Ficus thonningii contains various bioactive compounds which include alkaloids, terpenoids, flavonoids, tannins and active proteins, all of which contribute to its curative properties. In vitro and in vivo pharmacological studies revealed that F. thonningii possesses antimicrobial, antidiarrhoeal, antihelmintic, antioxidant, anti-inflammatory and analgesic properties. Acute and sub-chronic toxicity studies have shown that Ficus thonningii is non-toxic if administered orally in low doses. Scientific research has validated the ethnomedicinal claims that Ficus thonningii is useful in disease management. However, there is need to continue identifying, isolating and quantifying the active principles and possibly determine the mechanisms underlying its curative properties.